Studi eksperimental pemantauan kondisi dan penilaian analisa kinematik pengereman mobil - Muhammad Sabri; Ardhian Fauza (Badan Kerja Sama Teknik Mesin Indonesia, 2017)
Braking is an activity that aims to stop, handle and control the vehicle through the wheels. This study conducted experimentaly on four-wheeled vehicle brakes. The purpose is to find the relationship between the main parameters of the force, distance and time on the braking process. The results showed that the force parameters were inversely proportional to the distance and braking time. It will be an indicator of the brake performance to control vehicle base on road condition.